Similipecten colmani Dijkstra & Beu 2018, sp. nov. - Dijkstra, Henk H.; Beu, Alan G. (Zenodo, 2018)
Similipecten colmani sp. nov. Figs 19E–I, 20 Holotype (lv) AM C.165504, Arafura Sea, Northern Territory, c. 45 ml N of Croker Island, 10°17'S 132°38'E, dead, 65 m, leg. P. H. Colman, 9 Nov 1969, MV San Pedro Sound (H 3.0 mm, L 3.4 mm). Paratypes c. 100 (v), AM C.209771 (lv & rv), ZMA Moll.409004 (3 lv and 3 rv), same locality data as holotype. Additional material examined . — AUSTRALIA: QUEENSLAND : N Gulf of Carpentaria, 11°07'S 139°32'E, dead, 59 m (4 v, C.165497); NE Gulf of Carpentaria, 11°56'S 140°25'E,dead, 67 m (1 v,C.165495); Central Gulf of Carpentaria, 14°29.5'S 138°14'E,dead, 60 m (1 v,C.165496). WESTERN AUSTRALIA : off North West Cape, 22°51'S 113°41.2'E, dead, 78 m (2 v, C.165512); c. 190 ml NW of Port Hedland, 19°32'S 115°49'E, dead, 183 m (2 v, C.165491 [in part]); N of Port Hedland, 18°40'S 117°55'E, dead, 150 m (3 v, C.157678 [in part]); c. 135 ml NW of Roebuck Bay, 17°34'S 120°22'E,dead, 188 m (4 v,C.165508); c. 100ml NW of Broome, 16°58'S 120°47'E, dead, 194 m, 5 v (5 v, C.165510; 4 v, C.165511); c. 240 ml NE of Broome, 14°37'S 123°40'E, dead, 80 m (1 v, C.165494 [in part]). NORTHERN TERRITORY : 100 km NE of Melville Island, 10°22.5'S 131°37'E, dead, 71 m (4 v, C.165506); 68 km NE of Croker Island, 10°39'S 133°05'E, dead, 62 m (4 v, C.165507); Arnhem Land, c. 60 ml NE of Goulburn Islands, 11°08'S 134°18.5'E,dead, 50 m (1 v,C.165501); Arnhem Land, 365 km N of Miinggimbi Island, 8°48'S 134°58'E, dead, 100 m (1 v, C.165502); c. 190 ml NW of Gove, 10°16'S 135°09'E, dead, 60 m (1 v, C.165505); Arnhem Land, c. 200 ml NW of Wessel Islands, 8°39'S 135°21'E,dead, 65 m (4 v, C.165499); Arnhem Land, N of Wessel Islands, 8°26'S 135°22'E, dead, 75 m, (1 v, C.165500); c. 250 ml NE of Croker Island, 9°11'S 135°43'E,dead, 70 m (1 v, C.165505); N of Arnhem Land, 10°50'S 137°10'E, dead, 59 m (1 v, C.165498). Description . Shell small, fragile, hyaline or opaque, triangularly subcircular, somewhat wider than high, rather compressed, inequilateral, auricles unequal in size and proportions; posterior ones longer, taller, weakly differentiated from disc, with weakly concave posterior margin, anterior ones with obvious, narrow byssal notch (right valve) or shallow byssal sinus (left valve); umbonal angle c. 90°. Stained milky white. Exterior of left valve disc sculptured with weak, closely spaced commarginal lirae towards ventral margin. Anterior auricle somewhat demarcated from shell disc, bearing c. 20 fine commarginal lamellae, prominent near disc flank. Antero-marginal area of anterior auricle somewhat curved, antero-dorsal area somewhat raised. Posterior auricle weakly demarcated from disc, bearing very weak, fine, close-set commarginal lirae; postero-dorsal margin straight. Additional description (paratypes, rv). Shell up to c. 4 mm high, hyaline or opaque, dull milky white without maculations, slightly more convex than left valve, sculptured with closely spaced commarginal lamellae or lirae, also very weak or even absent. Anterior auricle sharply demarcated from disc, with semicircular anterior end, beraing very closely spaced fine lirae, absent from some specimens. Posterior auricle weakly demarcated from disc, bearing same sculpture as disc. Byssal notch narrow. Figure 20 . Distribution of Similipecten colmani sp. nov. (circles), Catillopecten murrayi (Smith) (star) and C. tasmani Dijkstra & Marshall (triangle). Discussion . A similar-looking species, Similipecten eous (Melvill in Melvill & Standen, 1907), from the Red Sea and Arabian Sea, differs from the present species in its very weak sculpture of commarginal growth lines or a smooth shell surface on the left valve in early growth stages. The present species has more prominent sculpture of commarginal lirae on the left valve. The exterior surface of the right valve of S. colmani has commarginal lamellae or lirae, whereas it is smooth in S. eous. Similipecten similis (Laskey, 1811) from the eastern Atlantic is larger (up to c. 6 mm in height), more brightly coloured on the left valve and most specimens have completely smooth discs on both valves. Habitat . Dead specimens only collected so far, in the sublittoral and bathyal zones on soft sediment (sand and clay). The presence of an obvious byssal notch indicates that Similipecten colmani sp. nov. lives byssaly attached to hard objects. Ockelmann (1958: 68–72) described the byssal attachment of Similipecten greenlandicus [under Propeamussium ( Arctinula )]: “Several adult animals were found with a bundle of exceedingly fine byssus threads, and possibly the species, when undisturbed, normally lives attached to objects on the sea bottom”. Distribution . Similipecten colmani sp. nov. is distributed from off North West Cape (Western Australia) northeastwards to the Arafura Sea in the Gulf of Carpentaria (Queensland). Probably also from the Flores Sea and Savu Sea (Indonesia) (see Remarks). So far only empty specimens have been collected, in a bathymetric range of 50– 194 m. Remarks . It is most likely that the specimens with abraded sculpture from Indonesia, identified as Similipecten eous by Dijkstra (1991: 23) are also this species. Etymology . Named after Mr Phil H. Colman, senior technical officer in the Malacology Department of the Australian Museum, Sydney (now retired), who collected many pectinoids treated in this project and provided valuable ecological data from his field books. : Published as part of Dijkstra, Henk H. & Beu, Alan G., 2018, Living Scallops of Australia and Adjacent Waters (Mollusca: Bivalvia: Pectinoidea: Propeamussiidae, Cyclochlamydidae and Pectinidae), pp. 113-330 in Records of the Australian Museum (Rec. Aust. Mus.) (Rec. Aust. Mus.) 70 (2) on page 154, DOI: 10.3853/j.2201-4349.70.2018.1670, http://zenodo.org/record/5299017 : {"references": ["Laskey, J. 1811. Account of north British Testacea. Memoirs of the Wernerian Natural History Society 1: 370 - 417.", "Ockelmann, K. W. 1958. The zoology of East Greenland. Marine lamellibranchs. Meddelelser om GrOnland 122 (4): 1 - 256."]}